2014
DOI: 10.2105/ajph.2014.301969
|View full text |Cite
|
Sign up to set email alerts
|

Role of Health Insurance on the Survival of Infants With Congenital Heart Defects

Abstract: Objectives We examined the association between health insurance and survival of infants with congenital heart defects (CHDs), and whether medical insurance type contributed to racial/ethnic disparities in survival. Methods We conducted a population-based, retrospective study on a cohort of Florida resident infants born with CHDs between 1998 and 2007. We estimated neonatal, post-neonatal, and infant survival probabilities and adjusted hazard ratios (AHRs) for individual characteristics. Results Uninsured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 48 publications
3
49
0
Order By: Relevance
“…Although we did not have information on the medical insurance status of infants, previous studies found that medical insurance explained some of the observed racial/ethnic disparities. 16,57 Therefore, it is plausible that referral patterns and access to and use of advances in pediatric cardiac care may be important predictors of disparity in survival among infants with a CHD, and that addressing these issues might be an important step in reducing these disparities. Because survival estimates vary across CHD subtypes, there might be a concern that unequal distribution of subtypes by race/ethnicity could explain differences in survival by race and ethnicity; however, a previous study showed modest variation in birth prevalence by race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not have information on the medical insurance status of infants, previous studies found that medical insurance explained some of the observed racial/ethnic disparities. 16,57 Therefore, it is plausible that referral patterns and access to and use of advances in pediatric cardiac care may be important predictors of disparity in survival among infants with a CHD, and that addressing these issues might be an important step in reducing these disparities. Because survival estimates vary across CHD subtypes, there might be a concern that unequal distribution of subtypes by race/ethnicity could explain differences in survival by race and ethnicity; however, a previous study showed modest variation in birth prevalence by race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nonmedical factors (particularly race/ethnicity) also play an important role in the survival of infants with birth defects and potentially contribute significantly to unexplained survival differences. 8 Several factors that influence access to and use of care have been examined among cohorts of infants born with CHDs, but these have been limited to race/ethnicity, 2,916 medical insurance, 9,1620 and distance to specialty care. 10,17,21,22 Assessment of the potential impact of socioeconomic status (SES) on survival has been challenging, largely because SES has been defined and measured in many ways and is often unavailable in large, population-based data sets.…”
mentioning
confidence: 99%
“…22-24 Previous literature suggests that the mortality and survival experience of children with birth defects differs by specific birth defect phenotype and by demographic factors such as maternal race/ethnicity. 12-14,25-28 Racial/ethnic disparities in infant and child mortality were found among Florida 29 and Texas infants with birth defects 25,27,28 but not among New York children (up to 25 years) with birth defects. 12 …”
mentioning
confidence: 95%
“…The living conditions of the mother at the time of conception, such as her health status, nutritional condition, educational and socioeconomic level, age, number of previous children, number of prenatal visits and type of insurance, among other factors, can critically influence the perinatal outcome. These factors may precipitate a specific exposure such as diabetes or drug use in the periconceptional period and affect the development of the embryo in the period of organogenesis 12 13. Both mothers in the cases reported lived in a city where the entire population is of low socioeconomic status living under conditions of extreme poverty.…”
Section: Global Health Problem Analysismentioning
confidence: 98%